Our first lady of art : critiquing the memory of Georgette Chen - Lee, Sheryl Ke Ying (2016)
The National Gallery was launched in 2015 as part of Singapore’s sustained policy efforts to promote itself as a global city for the arts. Central to this cultural invigoration is Georgette Chen, a Nanyang Pioneer artist who contributed significantly to the development of the Nanyang Art style. Despite having been out of public view for the past two decades since her death, the memory of her has resurfaced, and her image has been widely proliferated as part of the Gallery’s recent publicity efforts. However, one realizes that even though she was revered by the state, the memory of her is gendered and subsumed under a national narrative that sought to legitimize Singapore’s art historical legacy. As such, this paper seeks to provide alternative propositions to nuance the gendered stance proposed by Jane Chia, as well as to critically examine the way in which the state and its state funded institutions might have constructed Georgette’s legacy to serve nationalistic purposes. Lastly, the paper will conclude with a reflection on how Georgette can be used as a case study to examine how sparse scholarship on women artists, a lack of consistency in writing, and limited platforms contributed to the truncated historiography of art in Singapore.